Produksi Ujaran Anak Tuna Grahita (Down Syndrome): sebuah Kajian Psikolinguistik pada SLB Mekar Sari 1 Cibinong - Wulan Yulian Anggini; Prima Pantau Putri Santosa (LITERATUS, 2022)
Children with mental retardation are those who experience disturbances in cognitive aspects. This will affect the process of acquisition and production of speech. This study aims to describe the forms of words and sentences that can be uttered by mentally retarded children, especially Down Syndrome, and the influence of the family environment on the development of their speech production. This research uses descriptive qualitative method. The focus of this research is how Down Syndrome children produce words and sentences. In addition, this study also looks at family environmental factor that can affect the process of producing words and sentences. This research was conducted on children with Down Syndrome aged 8 years at SLB Mekar Sari 1 Cibinong. Data collection was carried out through observation, interviews and literature studies. Then,  the data obtained are subjected to a reduction, presentation, and verification process. This study produced several findings; First, children with Down Syndrome at the grade 1 level (8 years) have not been able to produce many complete words. Second, they still need stimulation so that they are able to say simple words or sentences with the SPO (Subject, Predicate and Object) pattern.